Experimental investigation of four volumetric expanders. (September 2017) - Dumont, Olivier; Dickes, Rémi; Lemort, Vincent
Abstract: The aim of this paper is to facilitate the selection of the expander for a small-scale organic Rankine cycle based on an experimental comparison of a piston, a screw and two scroll expanders. First, based on a literature review, a comparison between these three technologies of volumetric expansion machines is performed. Afterward, four displacement expanders ( 2kW) are tested in a small-scale ORC unit with fluid R245fa: a variable speed swashplate piston prototype, an oil-free twin-screw, a modified lubricated hermetic scroll compressor operating at a constant speed and a variable speed modified scroll compressor. The maximum effective isentropic efficiencies measured are 53% for the piston expander and the screw expander, 76% for the variable-speed scroll and 81 % for the constant-speed scroll machine. However, these performance do not reflect the highest efficiencies achievable by each expander: the test-rig has experimental limitations in terms of mass flow rate and pressure drop (among others) which restrict the achievable operating conditions. The calibration of semi-empirical models based on the measurements allows to overcome this issue and to predict the isentropic efficiency in optimal conditions despite the limitations of the test-rig. When selecting an expander, other considerations than the efficiency have to be taken into account such as the flexibility, the operating conditions, the costs and the components compactness. Based on experimental results and practical considerations, some guidelines are drawn to help the reader to properly select a volumetric expander.